Socioeconomic and gender inequalities in childhood obesity in Spain - Enrique Gutiérrez-González; Francisco Sánchez Arenas; Ana María López-Sobaler; Blanca Andreu Ivorra; Almudena Rollán Gordo; Marta García-Solano (Elsevier, 2023)
Introduction: Childhood obesity is inversely associated with household socioeconomic status in high-income countries. Our aim was to explore the association between childhood weight status and household socioeconomic status in Spain in relation to family characteristics, perceptions and lifestyle habits and the school environment. Methods: We performed a descriptive analysis of child weight status according to family socioeconomic factors and mediating variables based on data from the ALADINO 2019 study in a sample of 16,665 schoolchildren representative of the population aged 6-9 years in Spain. Results: The prevalence of childhood obesity in households with low socioeconomic status (26.8% boys; 20.4% girls) was, in both sexes, twice as high as in those with higher socioeconomic status (12.1% boys; 8.7% girls). Unhealthy eating habits, sedentary lifestyles (mainly in girls) and the presence of screens in the bedroom (more prevalent in boys) were more frequent in school-aged children from low-income households. On the other hand, in the most disadvantaged households, a history of breastfeeding and physical activity (especially in girls) were less frequent. Similarly, schools attended by children from low-income households were less likely to have their own kitchens and indoor gymnasiums or offer sports activities. Conclusion: A lower household socioeconomic status was associated with poorer dietary and physical activity habits and certain characteristics of the family and school environments that mediate the inverse association between household socioeconomic status and the prevalence of childhood obesity. Girls were less physically active and reported more sedentary lifestyles, while boys had greater access to screens. Interventions to combat childhood obesity should address the identified inequalities. Resumen: Introducción: La obesidad infantil se asocia inversamente con el nivel socioeconómico familiar en países desarrollados. El objetivo es evaluar la asociación entre la situación ponderal infantil y el nivel socioeconómico familiar, según características familiares, percepciones, hábitos de vida y entorno escolar. Metodología: Análisis descriptivo de la situación ponderal infantil según factores socioeconómicos familiares y variables mediadoras en el estudio ALADINO 2019, en una muestra de 16.665 escolares representativa de la población escolar de 6 a 9 años en España. Resultados: La prevalencia de obesidad infantil en hogares de bajo nivel socioeconómico (26,8% niños; 20,4% niñas) era, en ambos sexos, el doble de la de los de mayor nivel (12,1% niños; 8,7% niñas). En escolares de familias de baja renta eran más frecuentes hábitos alimentarios poco saludables, el sedentarismo (principalmente en niñas) y la presencia de pantallas en la habitación (más en niños). Por el contrario, en hogares más desfavorecidos eran menos frecuentes el antecedente de lactancia materna y la práctica de actividad física (especialmente en niñas). La disponibilidad de cocina propia, actividades deportivas y gimnasio cubierto en los centros era también menos habitual para los escolares de familias de menor renta. Conclusiones: Un menor nivel socioeconómico del hogar se asocia con peores hábitos alimentarios y de actividad física y ciertas características del entorno familiar y el escolar, que a su vez median la asociación inversa que existe entre el nivel socioeconómico y la prevalencia de obesidad infantil. Las niñas realizan menos actividad física y presentan más sedentarismo mientras que los niños tienen más acceso a pantallas. Las intervenciones para combatir la obesidad infantil deben contemplar las desigualdades identificadas.